Can Comprehensive Geriatric Assessment Meet Frail Older People’s Needs? Results from the Randomized Controlled Study CGA-Swed - Theresa Westgård (Geriatrics, 2020)
Background: The comprehensive geriatric assessment (CGA) designed to manage frail older people requiring acute medical care, is responsible for diagnostics, assessment, treatment, and planning while addressing a person’s medical, psychological, social, and functional capabilities. The aim was to investigate if CGA had an impact on frail older people’s activities of daily living (ADL) status, self-rated health, and satisfaction with hospital care. Methods: A two-armed design with frail people aged 75 or older who required an unplanned hospital admission were randomized to either the CGA ward or to an acute medical ward. Analyses were made based on the intention-to-treat principle (ITT). The primary outcome was ADL. Data were analyzed using Chi-square and odds ratio. A subgroup analysis was performed due to non-adherence and contamination. Results: One-hundred and fifty-five people participated in the study; 78 in the intervention and 77 in the control. Participants in the intervention group had a higher odds ratio of reporting having received written information and felt that care met their needs during their hospital stay. No additional statistically significant results for the primary or secondary outcomes in the ITT analysis were achieved. Conclusion: Participants felt that the care they received with the CGA ward met their needs. The lack of additional results supporting the CGA could be due to difficulties performing pragmatic intervention trials in clinical hospital settings, and because a CGA during one hospital stay is probably not enough to have long-term effects.